2004
DOI: 10.1051/limn/2004018
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton biomass in an eutrophic shallow lake (Buenos Aires, Argentina): spatio-temporal variations

Abstract: in a shallow eutrophic lake (San Miguel del Monte, Argentina). Duplicate samples of zooplankton were obtained from three stations with different limnological characteristics. The density of zooplankton community was dominated by rotifers and small cladocerans related to the trophic status of this shallow lake. The zooplankton biomass showed similar values to other eutrophic shallow lakes. The annual biomass distribution was bimodal (winter and summer peaks). The contribution of crustaceans, mainly copepods, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
1
8
0
3
Order By: Relevance
“…The zooplankton composition of Lacombe Lake appears to be similar to that described for other pampean lakes (Boltovskoy, Dippolito, Foggetta, Gómez & Alvarez 1990; Benítez & Claps 2000; Gabellone, Solari & Claps 2001). Likewise, although there is not much information about zooplankton biomass in pampean shallow lakes, the biomass found in this study (maximum biomass in the lake: 3269 μg dw L −1 ) is comparable with that from other eutrophic shallow environments of Argentina (maximum biomass: 3987 μg dw L −1 ) (Claps et al . 2004).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The zooplankton composition of Lacombe Lake appears to be similar to that described for other pampean lakes (Boltovskoy, Dippolito, Foggetta, Gómez & Alvarez 1990; Benítez & Claps 2000; Gabellone, Solari & Claps 2001). Likewise, although there is not much information about zooplankton biomass in pampean shallow lakes, the biomass found in this study (maximum biomass in the lake: 3269 μg dw L −1 ) is comparable with that from other eutrophic shallow environments of Argentina (maximum biomass: 3987 μg dw L −1 ) (Claps et al . 2004).…”
Section: Discussionsupporting
confidence: 76%
“…In the case of zooplanktivorous fish, it is necessary to assess how hydrodynamic conditions and lake morphology might affect zooplankton distribution. For example, in another pampean lake, the Lake Monte, Claps et al . (2004) found that zooplankton distribution differed within the lake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La Salada de Monasterio Lake showed similar limnological and zooplankton community features to other Pampean lakes (Claps et al . ; Colautti et al . ; Diovisalvi, Berasain, Unrein, Colautti, Fermani, Llames, Torremorell, Lagomarsino, Pérez, Escaray, Bustingorry, Ferraro & Zagarese ).…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that the pejerrey extensive cage culture can also reduce costs by not demanding constant attention from staff and not relying on artificial energy supplies, but being mainly dependent on the natural food, in quantity and quality. Since pejerrey feeds on zooplankton (Destefanis & Freyre ; Ringuelet, Iriart & Escalante; Freyre, Colautti, Maroñas, Sendra & Remes Lenicov ), extensive cage culture can take advantage of natural high productivity exhibited by most of the Pampean lakes (Quirós & Drago ; Escalante ; Quirós, Rennella, Boveri, Rosso & Sosnovsky ; Claps, Gabellone & Benítez ), avoiding the provision of artificially cultured living food, which is essential for weaning and for optimal development in early stages.…”
Section: Introductionmentioning
confidence: 99%